Relationship between physical training, ratings of perceived exertion, and mental toughness in female NCAA Division I volleyball players - Castello, M.; Reed, J. P.; Lund, R.; Mack, M. (The Sport Journal, 2018)
The purpose of this study was to examine the relationship between participating in a conditioning program, ratings of perceived exertion, heart rate (HR), and mental toughness. Thirteen Division I Volleyball players were recruited while 10 participated in an 8-week off-season conditioning program aimed at improving physical fitness. Before and after the training period, the Yo-Yo intermittent recovery test and Mental, Emotional, and Bodily Toughness Inventory (MeBTough) were completed. While performing the Yo-Yo intermittent recovery test, heart rate was collected. During the 8-week program, session rating of perceived exertion (sRPE) was obtained following each training session. Significant improvement in physiological capacity was observed following the 8-week training protocol; pre (844m ± 196.37) to post (980m ± 200.67), t(9) = -5.50, p = 0.00. Mental toughness scores (as assessed by the MeBTough) did not change significantly during that same time period; pre (145.2 ± 12.3) to post (144 ± 16.72), p > 0.05. Additionally, no significant correlation between the capacity to perform on the physical test, the mental toughness score, sRPE, or maximum HR was found.